ANALISIS PEMAHAMAN KONSEP PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL BERDASARKAN TEORI APOS - Ida Silfia; Yuniar Ika Putri Pranyata (SIGMA, 2021)
This research aims to describe the analysis of students to understand the concept of the Three Variable Linear Equation System (SPLTV) based on the APOS theory (Action, Process, Object and Schema). This research did in the three students class X of MA Miftahul Huda Kepanjen. With students high (A), medium (B) and low ability categories(C). The results of the study show that highly capable subjects have an understanding of the stages of APOS (action, processes, objects and schemes). Subjects who are capable of having did’t understanding at the stage of process. While low-ability subjects have an understanding of the stages of action. In this description get node action the students tight with to understand the concept of the materi. So, researcher proposition of the teacher for notice the process materi in this study mathematics.